Problem-Based Learning Model Using Local Balinese Wisdom Against Elementary School Students' Science Misconceptions - Astuti, Putu Yulia; Werang, Basilius Redan (Mimbar Ilmu, 2023)
Science learning activities in elementary schools (SD) still need to run effectively. Teachers' choice of an inappropriate learning model in teaching students causes students to need help understanding the material being taught well. This research investigates and analyses the strong influence of the problem-based learning model based on Balinese local wisdom on the significant reduction in science misconceptions in Class V elementary school students. This research is quasi-experimental, with a non-equivalent post-test-only control group design. The population is 203 students from 8 elementary schools (SD). The sample in this study was 32 experimental class students and 30 control class students who had previously been determined using random sampling techniques. Data on students' science misconceptions was obtained using the objective test method followed by the CRI (Certainty of Response Index) method and analysed using the two-way ANOVA test. The average science misconception of experimental class students was 7.78 in the low category, and the control class was 10.73 in the low sort. Inferential statistical analysis showed that the significance value was 0.000, less than 0.05 (0.000, less than 0.05). The research concludes a significant difference in science misconceptions between students who follow the problem-based learning model based on local Balinese wisdom and those who follow the conventional model in fifth-grade elementary school students.